2008
DOI: 10.1016/j.febslet.2008.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Loss of expression of N‐acetylglucosaminyltransferase Va results in altered gene expression of glycosyltransferases and galectins

Abstract: We isolated mouse embryo fibroblasts (MEFs) from N-acetylglucosaminyltransferase Va (GnT-Va) knockout mice and studied the effects of loss of expression of GnT-Va on asparagine-linked glycans (N-glycan) synthesis and the gene expression of groups of glycosyltransferases and galectins. Loss of GnT-Va expression caused aberrant expression of several N-glycan structures, including N-linked b(1,6) branching, poly-N-lactosamine, bisecting N-acetylglucosamine (GlcNAc) and sialic acid. Using quantitative reverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Many published studies have reported statistically and biologically significant microarray data using a low cutoff rate similar to that used in the present study 21-26. Moreover, many differential gene expression studies have shown low changes in glycogenes, specifically glycosyltransferases, to be biologically relevant 27-30. For example, Comelli et al29 showed that a 1.3- to 1.5-fold decrease in ST3GalI expression between fresh and activated T cells (and B cells) is sufficient to cause hyposialylation of O-glycans.…”
Section: Discussionmentioning
confidence: 83%
“…Many published studies have reported statistically and biologically significant microarray data using a low cutoff rate similar to that used in the present study 21-26. Moreover, many differential gene expression studies have shown low changes in glycogenes, specifically glycosyltransferases, to be biologically relevant 27-30. For example, Comelli et al29 showed that a 1.3- to 1.5-fold decrease in ST3GalI expression between fresh and activated T cells (and B cells) is sufficient to cause hyposialylation of O-glycans.…”
Section: Discussionmentioning
confidence: 83%
“…1-β-1,4-GalT V). As ablation of the N -acetylglucosaminyltransferase Va gene in mice affected the expression of several other glycosyltransferase genes [37], the expression levels of the β-1,4-GalT I, II, III, IV and VI genes were examined by RT-PCR. The results showed that no significant changes in their expression levels are observed among three samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been already known that β1,6GlcNAc branching of N-glycans is often increased [26] and the chain length of mucintype O-glycans is generally shorten in cancer patients, notably "aberrant O-glycans" [27]. Branching N-glycan structures, such as bisecting GlcNAc and third branching1,6GlcNAc are produced by enzymes GlcNAc-transferase-III (GnT-III) and GlcNAc-transferase-IV or -V (GnT-IV or -V), respectively.…”
Section: Discussionmentioning
confidence: 99%